Gsaṅ chen Sṅa-ʼgyur Rñiṅ-ma-paʼi gsuṅ rab phyogs bsgrigs dri med legs bśad kun ʼdus nor buʼi baṅ mdzod las / 10 Phar phyin / 'Ju Mi-pham sogs kyis mdzad - Rnam-rgyal-rgya-mtsho (Gsaṅ chen Sṅa-ʼgyur Rñiṅ-ma-paʼi gsuṅ rab phyogs bsgrigs dri med legs bśad kun ʼdus nor buʼi baṅ mdzod las, 2006)
Sammlung von Werken zur Prajñāpāramitā